การบริหารจัดการศูนย์พัฒนาเด็กเล็ก: องค์กรปกครองส่วนท้องถิ่นในอำเภอแม่แตง จังหวัดเชียงใหม่ - พงษ์เดช, เกษม; ศิริโวหาร, สุพรชัย; จุลจักรวัฒน์, จุไรรัตน์ (Ganesha Journal, 2015)
การวิจัยครั้งนี้ มีวัตถุประสงค์เพื่อศึกษาปัจจัยที่มีผลต่อความสำเร็จในการบริหารจัดการศูนย์พัฒนาเด็กเล็ก ขององค์กรปกครองส่วนท้องถิ่น เป็นการวิจัยภาคสนามแบบไม่ทดลอง กลุ่มตัวอย่างในการวิจัย คือ ผู้รับผิดชอบการบริหารจัดการศูนย์พัฒนาเด็ก ผู้ปฏิบัติงานประจำศูนย์พัฒนาเด็กและผู้ปกครองเด็กเล็กในอำเภอแม่แตง จังหวัดเชียงใหม่ ปี พ.ศ. 2554 จำนวน 395 คน ผลการวิจัย พบว่า ปัจจัยที่มีผลต่อความสำเร็จในการบริหารจัดการศูนย์พัฒนาเด็กเล็กขององค์กรปกครองส่วนท้องถิ่น มี 3 ปัจจัย เรียงลำดับความสัมพันธ์จากมากไปหาน้อย ได้แก่ 1) การมีส่วนร่วมของประชาชนในการจัดทำแผนงานศูนย์พัฒนาเด็กเล็ก 2) ทักษะและประสบการณ์การสอนที่ดีของผู้ดูแลเด็ก 3) การจัดสรรงบประมาณขององค์กรปกครองส่วนท้องถิ่นให้กับศูนย์พัฒนาเด็กเล็กที่เพียงพอและเหมาะสม การบริหารจัดการศูนย์พัฒนาเด็กเล็กขององค์การปกครองส่วนท้องถิ่นในอำเภอแม่แตง จังหวัดเชียงใหม่ ปี พ.ศ. 2554 มีความสำเร็จระดับมาก MANAGEMENT OF CHILD DEVELOPMENT CENTER: L0CAL ADMINISTRATIVE ORGANIZATION MAE TAENG DISTRICT, CHIANGMAI PROVINCE. The purpose of this research was to study affecting factors on management success of child development center of Local Administrative Organization. This research was a field research as non-experimental design. Sample group was 395 people who were administrators of child development centers, employees of child development centers, and parents of young children in Mae Taeng District, Chiang Mai Province. The results of this research found that there were three factors affected on management success of child development center of Local Administrative Organization at statistically significant level of 0.05 with correlation from high to low respectively as follows: 1) Participation of people to make action plan of child development center 2) Good skills and teaching experiences of child care employees 3) Local administrative organization allocated sufficient and suitable budget for child development center. The success of child development center of Local Administrative Organization in Mae Taeng District, Chiang Mai Province in the year 2011 was high level.